Business Innovation and the Law : perspectives from Intellectual Property, Labour, Competition and Corporate Law - Pittard, Marilyn; Monotti, Ann L.; Duns, John (Elgar Publishing Ltd, 2013)
Contents: Preface PART I: BUSINESS INNOVATION: INTRODUCING THE PERSPECTIVES 1. Perspectives and Themes John Duns, Ann L. Monotti and Marilyn Pittard 2. Failed Collaborations: The Misappropriation of Business Opportunities, Ideas and Advantages by Prospective Co-venturers, Financiers and Brokers Paul Finn PART II: INVENTIONS AND DISCOVERIES IN BUSINESS: INTELLECTUAL PROPERTY PERSPECTIVES 3. Innovation through the Lens of Intellectual Property Law: Rights in Employee Inventions Ann L. Monotti 4. Double or Nothing: Technology Transfer under the Bayh-Dole Act Rochelle Cooper Dreyfuss 5. Establishing Clear Rights in Academic Employee Inventions: Lessons Learnt from University of Western Australia v Gray Ann L. Monotti 6. Professional and Academic Employee Inventions: Looking Beyond the UK Paradigm Justine Pila 7. EU Perspectives on Employees Inventions Marie-Christine Janssens PART III: THE EMPLOYMENT AND LABOUR LAW PERSPECTIVE ON PROTECTING BUSINESS RESEARCH AND DEVELOPMENT 8. Innovation through the Lens of Labour and Employment Law Marilyn Pittard 9. Resolving Invention Ownership Disputes: Limitations of the Contract of Employment Mark Freedland and Jeremias Prassl 10. The Innovative Worker: Genius, Accidental Inventor or Thief? Marilyn Pittard 11. Employees Inventions and the Employment Contract: A European Union Perspective Riccardo Del Punta 12. US Employment Law Perspectives on the Issue of Who Owns an Employees Invention Richard Bales 13. Taking the Long View on Competition and the Mobile Employee: Lessons from the United States History of Efforts to Regulate Employee Innovation and the Mobility of Workplace Knowledge Catherine L. Fisk PART IV: THE COMPETITION LAW PERSPECTIVE ON PROTECTING BUSINESS RESEARCH AND DEVELOPMENT 14. Innovation through the Lens of Competition Law John Duns 15. Legal Protection of Business Research and Development: Can it Harm Competition? Ray Finkelstein 16. Business Innovation and Competition Law: An Australian Perspective John Duns 17. Perspectives from Competition Law Practice Dorothy Livingston 18. EU Competition Law, and Research and Development Agreements Rosa Greaves PART V: DEVICES TO PROTECT BUSINESS RESEARCH AND DEVELOPMENT FROM INTERNAL ATTACK 19. Devices at Law to Protect Employers: A Conspectus of Approaches Marilyn Pittard 20. Devices to Restrain Competition and Protect Discoveries and Enforcement: Workplace Policies and Confidentiality Agreements John Hull 21. Devices to Restrain Competition and Protect Discoveries and Enforcement: Confidentiality in the Courts and Europe Alison Firth 22. Devices to Restrain Competition and Protect Confidential Information in Employment Practical and Legal Aspects: An Australian Perspective Chris Molnar 23. The Law and Policy of Non-compete Clauses in the United States and their Implications Jay P. Kesan and Carol M. Hayes PART VI: PUBLIC SECTOR BUSINESS RESEARCH AND DEVELOPMENT 24. Innovation in Public Sector Research Ann L. Monotti 25. Technology Transfer Law, Policies and Practices at the U.S. National Institutes of Health Claire T. Driscoll 26. Licensing University Intellectual Property: Ownership and Management of Intellectual Property in the United Kingdom Noel Byrne PART VII: CORPORATE GOVERNANCE ISSUES AND INNOVATION 27. Innovation through the Lens of Corporate Governance John Duns 28. Institutions and Innovation: Is Corporate Governance the Missing Link? Simon Deakin and Andrea Mina
Keywords: LIIKE-ELÄMÄ; LIIKETOIMINTA; LAINSÄÄDÄNTÖ; IMMATERIAALIOIKEUS; TYÖNTEKIJÄT; KILPAILU